High-precision 40Ar/39Ar age of the Jänisjärvi impact structure (Russia) - Jourdan, Fred; Renne, P.; Reimold, U. (Elsevier Science BV, 2008)
The ~14 km diameter Jnisjrvi impact structure is located in Svecofennian Proterozoic terrain in the southeastern part of the Baltic shield, Karelia, Russia. Previous radioisotopic dating attempts gave K/Ar and 40Ar/39Ar ages of 700 ± 5 Ma and 698 ± 22 Ma, respectively, with both results being difficult to interpret. Recent paleomagnetic results have challenged these ages and proposed instead ages of either 500 Ma or 850-900 Ma. In order to better constrain the age of the Jnisjrvi impact structure, we present new 40Ar/39Ar data for the Jnisjrvi impact melt rock. We obtained five concordant isochron ages that yield a combined isochron age of 682 ± 4 Ma (2s) with a MSWD of 1.2, P=0.14, and 40Ar/36Ar intercept of 475 ± 3. We suggest that this date indicates the age of the impact and therefore can be used in conjunction with existing paleomagnetic results to define the position of the Baltica paleocontinent at that time. Argon isotopic results imply that melt homogenization was achieved at the hundred-micrometer scale certainly, because of the low-silica content of the molten target rock that allows fast 40Ar* diffusion in the melt. However, the large range of F(40Ar* inherited) (4.1% to 11.0%) observed for seven grains shows that complete isotopic homogenization was not reached at the centimeter and perhaps the millimeter scale. The F(40Ar*inherited) results are also in good agreement with previous Rb and Sr isotopic data.